B-learning in english language teaching in higher education: a systematic review (Revista Innova Educación, 2022)
B-learning is widely regarded as an approach that combines the benefits of both the online and face-to-face learning components. However, the combination of online and face-to-face instructional components of this approach has raised concerns over the years. The following systematic review aims to show how b-learning influences the teaching of the English language in university students through the analysis of experiences and perceptions. The use of the Prism methodology has been considered for research purposes. For this review, the following databases were used: Scopus, Scielo, Science direct and Redalyc, finding 260 articles and selecting 16 articles for an in-depth review. The results show that most of the experiences with blended learning were beneficial in the field of teaching English. In addition, teacher and student perceptions are positive and decisive for the future use of digital technologies. This review highlights the need to carry out research that proposes solutions to address the challenges of students, teachers and educational institutions in blended learning, as well as the determination of characteristics of the model for an accessible implementation in the classroom
Keywords: Blended learning; educational technology; English teaching; higher-education